EFFECT OF PROPOSED PROGRAM OF PATIENT SAFETY ON NURSE’S KNOWLEDGE AND QUALITY OF CARE AT KOSTI AND RABAK TEACHING HOSPITALS-SUDAN - Mukhtar, Hayat Fadllalah; Ahmed, Mohammed Ibrahim Osman (International Journal of Research -GRANTHAALAYAH, 2019)
Background: The profession of Nursing has been at the forefront of patient safety taking special attention to the training and education of its workforce. Internationally, the International Council of Nurses (ICN) has been tackling this issue with force since it established that Patient safety is fundamental to quality health and nursing care Aim: To study the impact of a design propose program for nurses about patient safety and evaluate the impact of it on nurses knowledge. Methodology: This was quiz experimental study, one hundred eight nurses were included as all the entire population meeting the inclusion criteria taken as a sample, using census to achieve a desirable level of precision, the data was collected in four phases using a self-administered questionnaire, phase one include an orientation about the training program. Phase two (pretest data), in which the questionnaire was distributed for nurses and each one was allowed sufficient time to fill it. After collection of pretest data the nurses were received the training program, the training was continued for four months. Phase three: A posttest was obtained from the participants at the end of the program, the same self-administrative questionnaire. Follow up phase include the same process in phase three after one, two and three months to make sure of the consistency. The data was analyzed by (SPSS) program with (P. value, mean, standard deviation, T. test and chi squire test). Results: The present study revealed that the nurse’s knowledge were improved affected by the proposed training program. The mean of nurse’s knowledge regarding maintain patient safety was improved ,in pre intervention ( 3.77 +/- Std 1.24 ) to be ( 4.44 +/- Std 0.60 ) in posttest I which get better to ( 4.93 +/- Std 0.283 ) in posttest II , and it was ( 4.13 +/- Std 0.613 ) in posttest III, there was highly statistically significant association between the nurses knowledge and application of training program (p=0.000). Recommendations: Great emphasis should be directed towards the educational aspects on patient safety by providing educational posters, guidelines, pamphlets, manual and modern educational facilities, collaboration should be encourage between institutions and federal ministry of health to formalize a protocol of patient safety.